(untitled) (Web of Teachers: Inderscience Research, 2025)
In this article we saw the rapid technological changes of modern society significantly influence children’s socialization and emotional development. For primary school students, emotional competence becomes essential, as this age marks the beginning of forming communication skills, self-regulation, and emotional awareness. Artistic activity plays an important role in this process by enabling children to express their inner experiences and understand the emotions of others. The study examines how different types of visual arts contribute to the development of emotional competence among younger schoolchildren, taking into account individual psychological characteristics and gender differences.